2004
DOI: 10.2105/ajph.94.10.1713
|View full text |Cite
|
Sign up to set email alerts
|

Education-Related Gender Differences in Health in Rural China

Abstract: We investigated gender differences in education-related health inequalities in rural China. Household interview data were obtained from 6 provinces in 1993 and 2001. Remarkable health inequalities existed and favored the higher educational groups; among women, the inequalities were greater and health inequalities increased from 1993 to 2001. Education serves as a more powerful mediating factor for health inequalities among women than among men in rural China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…19 For the gender-specific association, the potential mechanisms are unknown. However, it is possible that the gender differences in psychosocial factors 50 and in stress and responses to stress 51 may have a role in the association. Another explanation may be that women in menopause tend to be more vulnerable because of fluctuations in sex hormones.…”
Section: Discussionmentioning
confidence: 99%
“…19 For the gender-specific association, the potential mechanisms are unknown. However, it is possible that the gender differences in psychosocial factors 50 and in stress and responses to stress 51 may have a role in the association. Another explanation may be that women in menopause tend to be more vulnerable because of fluctuations in sex hormones.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major findings from this study is that the mean of GII is greater among Africa than among other WHO regions in worldwide. Generally, gender inequalities in worldwide may be explained by the differences between women and men in employment status, healthy life years, income, lifestyles, and use of health care services [10,14,17,29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are large discrepancies in employment status between the sexes in black South African adults [8]. In addition, rural Chinese women have a significantly lower educational level than men [10]. While gender differences in health, assessed in terms of mortality and morbidity, have been reported in most developed countries over recent decades [11], less attention has been paid to the pattern of health care services use.…”
Section: Introductionmentioning
confidence: 99%
“…Their study revealed that educational health inequalities were greater with regard to all causes of mortality in both men and women. A study in China 21 showed that people with lower educational levels were more likely to fall ill. We found that subjects who rated their living conditions as poor were significantly worse off in terms of SRH, which is consistent with previous studies investigating the link between neighborhood perception and subjective health status. 22,23 The causal mechanisms underlying social inequalities in health are complex.…”
Section: Discussionmentioning
confidence: 99%